Hidden messages in pinterest’s public health advertisements: a semiotic analysis - Sari, Ni Kadek Purnama; Suastini, Ni Wayan; Juniartha, I Wayan (Journal of Language and Applied Linguistics, 2022)
Advertisements are the media that used to promote a product, brand or service to a viewership to attract interest. The advertisement that used in this study is public health advertisement that can be found in Pinterest. Public health advertisement is aimed to provide information to the people about the idea of healthy life that would be benificial for society. Furthermore, this study combines verbal and nonverbal sign in order to give a certain effect to the advertisement. This study is aimed to describe the hidden messages that can be found in Pinterest’s public health advertisements. This study uses semiotics theory by Saussure (1983) and theory of meaning proposed by Barthes (1977) that supported by theory of color terms proposed by Wierzbicka (1996). The data were collected through observation method. In conducting this study, the descriptive qualitative method is used to analyze the data.The study concludes that both verbal and nonverbal signs found in each data carry hidden messages. In general, the advertisements convey the messages to encourage the readers to promote a healthy lifestyle that can be achieved through certain activities, namely, exercising regularly, eating healthy food, getting enough rest, and not doing the things that can harm their body as smoking cigarettes.